2020
DOI: 10.29252/ibj.24.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Potential Vaccines for Treating Crohn's Disease

Abstract: CD is an inflammatory disease of the GIT and can affect several parts of the digestive system. There is a relationship between impaired mucosal barrier in the GIT of IBD patients and the role of bacteria such as MAP in CD. Apart from different therapeutic approaches for treating CD, development of a vaccine is a novel modality. In the present article, most available therapeutic opportunities in the last decade, especially the possibility of vaccines against CD, are reviewed. According to the search, availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…In vitro studies have shown that serum IL-23 p19-specific IgG significantly suppresses IL-23-induced IL-17 production by splenocytes. In vivo evaluations of the vaccine’s effect on mice with chronic colitis indicated that vaccine-immunized mice exhibited a decrease in colon inflammation, collagen deposition, and levels of IL-23 and IL-12 cytokines compared with the control groups [ 178 , 179 ]. It appears possible to develop a vaccine that would help control immune responses in this inflammatory disease.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In vitro studies have shown that serum IL-23 p19-specific IgG significantly suppresses IL-23-induced IL-17 production by splenocytes. In vivo evaluations of the vaccine’s effect on mice with chronic colitis indicated that vaccine-immunized mice exhibited a decrease in colon inflammation, collagen deposition, and levels of IL-23 and IL-12 cytokines compared with the control groups [ 178 , 179 ]. It appears possible to develop a vaccine that would help control immune responses in this inflammatory disease.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Last but not least, in phase III, the effectiveness of the vaccine is verified to determine its effectiveness in preventing infection with the targeted virus [ 11 ]. A major difference though, is the preventive application of a vaccine [ 12 ]. This means that typically a large population of healthy people, often a group of high risk patients of the infection to be studied, are vaccinated to quantify the effect of vaccination on the probability of contracting the infection and the severity of its course [ 13 ].…”
Section: Introductionmentioning
confidence: 99%